Apoptosis: A Key Process That Trypanosoma cruzi Modulates as a Strategy to Perpetuate Infection - Diego Maurizio Coria-Paredes; Arturo A. Wilkins-Rodríguez; Laila Gutiérrez-Kobeh (Journal of Parasitology Research)
Apoptosis is a crucial host defense mechanism because it can trigger the immune response and get rid of infected cells. These important goals, among others, are achieved through a fine-tuned process that culminates in a quiet form of cell death. Apoptosis represents a hindrance for intracellular microorganisms that live inside cells. Nevertheless, they have developed strategies that allow them to survive in diverse microhabitats inside their hosts, avoiding the immune response defense mechanisms. A good example of this is the intracellular parasite Trypanosoma cruzi, which, thanks to various adaptations, manages to go through its life cycle passing through the digestive tract of hemiptera and mammalian blood to reach its destination: the cytoplasm of the cells it infects. T. cruzi causes Chagas disease or American trypanosomiasis that constitutes a major health issue worldwide with 6–7 million people currently infected and approximately 10,000 annual deaths. Infection with T. cruzi can cause an extensive range of disease going from acute to chronic forms such as the chronic chagasic cardiomyopathy. In the transition from one form to another, many factors are implicated where the host immune response and T. cruzi genetic diversity stand out. Being an intracellular parasite, T. cruzi must evade the host’s defense mechanisms to successfully establish an infection. Apoptosis represents one of these mechanisms, and T. cruzi has developed several strategies to inhibit or induce apoptosis depending on the cell context. Interestingly, in addition to the ability of T. cruzi to modulate host apoptosis, it can experience an apoptosis-like cell death. In this review, we describe apoptosis and its main paths of induction as well as basic aspects of the parasite and Chagas disease and examine how the regulation of apoptosis influences infection by this protozoan.